Synthesis of silica aerogel monoliths with controlled specific surface areas and pore sizes. (18th July 2017) - Gao, Bingying; Lu, Shaoxiang; Kalulu, Mulenga; Oderinde, Olayinka; Ren, Lili
Abstract: To replace traditional preparation methods of silica aerogels, a small-molecule 1, 2-epoxypropane (PO) has been introduced into the preparation process instead of using ammonia as the cross-linking agent, thus generating a lightweight, high porosity, and large surface area silica aerogel monolithic. We put forward a simple solution route for the chemical synthesis of silica aerogels, which was characterized by scanning electron microscopy (SEM), TEM, XRD, FTIR, thermogravimetric analysis (TGA) and the Brunauer–Emmett–Teller (BET) method In this paper, the effect of the amount of PO on the microstructure of silica aerogels is discussed. The BET surface areas and pore sizes of the resulting silica aerogels can be freely adjusted by changing the amount of PO, which will be helpful in promoting the development of silica aerogels to fabricate other porous materials with similar requirements. We also adopted a new organic solvent sublimation drying (OSSD) method to replace traditional expensive and dangerous drying methods such as critical point drying and freeze drying. This simple approach is easy to operate and has good repeatability, which will further facilitate actual applications of silica aerogels.